Seismic Analysis (Zone v) of RCC Building (G+5) with Shear Walls Using Staad. Pro Software (International Journal of Innovative Research in Engineering & Management, 2023)
An upright component of a seismic force resisting structure called a shear wall is made to protect  against in-plane lateral forces, which are often caused by  wind and seismic loads. The design of shear walls is  governed by the international residential code and the  international building code in many countries. A shear wall  may withstand loads that are equal to the wall’s plane. The  diaphragm shear is transferred to shear walls and other  vertical components of the seismic force-resisting system  via collectors, sometimes referred to as drag members. In  this study, we have chosen Seismic analysis (zone v) of  RCC building (G+5) with shear walls using STAAD. Pro  software The multistory building (G+5) is the subject of  analysis. The STAAD. Pro, Designing and Analysis  software is used to develop the 3D model of Shear wall and  Building. Giving it constraints that are based on the acting  seismic force and wind loads on buildings rendered the  nodes weak, so we added a shear wall to reinforce that  nodes. Following the inclusion of the building's shear wall  and analysis using STAAD. Pro in standard format. After  analyzing the effect & shear wall's position on the building  & comparing results with old building design without shear  wall, it was determined that the addition & location of shear  walls in multistory structures strengthens the structure's  weak points and enables it to withstand lateral loads, wind  loads, and earthquake loads.
Keywords: Multistory Structure; Seismic Force; STAAD. Pro; Shear-Wall